(untitled) (PerCursos, 2026)
This article is part of a broader research project focusing on urban policy in municipalities in the state of Santa Catarina, Brazil. The analysis was developed from two perspectives: (i) the normative design of the Master Plans and (ii) the presence of mechanisms for monitoring implementation. The study examines 243 current Master Plans and shows that, although most municipalities are already in their second revision cycle since the enactment of the City Statute in 2001, the plans are predominantly programmatic and have limited self-applicability. Additionally, despite most documents mentioning monitoring systems, the effective identification of such mechanisms proved rare. The results point to relevant issues and open up possibilities for investigation regarding the implementation, transparency, and evaluation of urban policy actions at the municipal level.